2021
DOI: 10.2106/jbjs.rvw.20.00232
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Nonoperative Treatment Following First-Time Anterior Shoulder Dislocation

Abstract: Background: There is an ongoing debate about whether to perform operative or nonoperative treatment following a first-time anterior dislocation or wait for recurrence before operating. The aim of this systematic review is to compare recurrence rates following operative treatment following first-time anterior dislocation (OTFD) with recurrence rates following (1) nonoperative treatment (NTFD) or (2) operative treatment after recurrent anterior dislocation (OTRD).Methods: A literature search was conducted by sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Young and active patients suffering from first-time anterior shoulder dislocation routinely undergo arthroscopic refixation of the antero-inferior labrum at our hospital [ 23 , 24 ]. Concomitant pathologies can also be addressed during this operative intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Young and active patients suffering from first-time anterior shoulder dislocation routinely undergo arthroscopic refixation of the antero-inferior labrum at our hospital [ 23 , 24 ]. Concomitant pathologies can also be addressed during this operative intervention.…”
Section: Methodsmentioning
confidence: 99%
“…There is an increasing body of literature investigating the benefits of early stabilization following a traumatic anterior shoulder dislocation, especially in younger patients 38-40 . A recent systematic review and meta-analysis found that operative treatment following a first-time dislocation yielded significantly lower recurrent instability rates (10%) at >10-year follow-up compared with nonoperative management (55% recurrence) 40 . Additionally, that study found that recurrence rates were also significantly different in patients who underwent operative treatment after their first dislocation compared with after multiple dislocations (17% in this pooled group).…”
Section: Discussionmentioning
confidence: 99%
“… 31 Patients with first-time dislocations who receive operative treatment are most often treated with labrum repair. 31 Risk factors associated with failure of an arthroscopic Bankart repair include young age (≤30 years), participation in competitive sports, multiple preoperative dislocations, >6 months surgical delay from first-time dislocation to surgery, ISIS >3 and associated lesions (Hill-Sachs, glenoid bone loss and anterior labrum periosteal sleeve avulsion (ALPSA) lesions. 19 It is impossible to take all these risk factors into account and make an objective decision on what treatment is most suitable.…”
Section: Discussionmentioning
confidence: 99%
“…Operative treatment significantly reduces the risk of recurrent shoulder instability compared with non-operative treatment 31. Patients with first-time dislocations who receive operative treatment are most often treated with labrum repair 31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation